Modelos espacio-temporales de factores de deterioro del recurso hídrico para la gestión integral de la cuenca del río mayo, san martin, 2006-2007 - Vergara Medrano, Segundo Edilberto (2010)
Space-temporal models of water resources disturb factors for integrated Mayo river watershed management were evaluate. In some way, this is a continuation of past expertise and earlier studies. Base on these experiences, it was proposed to value the spatial behavioural of factors that disturbed or influence on a negative way, the water resources of Mayo river. It was used the GIS; ILWIS v 3.6, Arc View GIS v 3.3 and Arc GIS v 9.2 to model and analysis of factors. The model of settlements spatial arrangement obtained from the analysis in relation to the area is cluster form arrangement, it means from a general point of view, they are closer each other. According to the technical of measure of arrangement and except to the settlements that match order four are distribute in a regular way (observed frequency is higher than the expected). The others settlement are dispersing in a cluster way. The observed media distance was shorter than the media distance expected in all cases. This does mean that settlements were found in a group arrangement way. The erosion on the riverside area in the Mayo River fluvial resulted in a high values (media of 4.1) within the 0-5 scale. Because of the geo morfo hydrological conditions of media basin, the erosion estimation at media watershed have not taken into consideration. Similar result did occur in lower basin. The highest solid waste generation was in San Martin with a production of 278 tn/day.